Cognitive and behavioral consequences of pediatric delirium: a pilot study - Meyburg, Jochen; Ries, Markus; Zielonka, Matthias; Koch, Karin; Sander, Anja; Haken, Rebecca von; Reuner, Gitta (Pediatric critical care medicine, 2018)
Objectives:To investigate the long-term impact of postoperative delirium in children.Design:Single-center point prevalence study.Setting:Twenty-two bed PICU.Patients:Forty-seven patients 1-16 years old.Interventions:Standardized neuropsychologic follow-up investigation after a mean time of 17.7 ± 2.
Gesehen am 19.02.2019